Detecting and Mitigating Social Dysfunction within Systems of Systems. Issue 3 (6th October 2021) - Yokell, Mike
ABSTRACT: What are systems engineers supposed to do when social dysfunction leads to operational dysfunction? This article elaborates on a means of assessing the managerial relationships between the organizations that own constituent systems (CS) within a system of systems (SoS), with a goal of detecting social dysfunction that could adversely affect operations. For each of the relationship types, or affinity options, tangible, actionable guidance is offered that could help mitigate the social and operational dysfunctions. Results from a case study are included to illustrate the application, detection, and successful mitigation of social dysfunction within a system of systems.